Organic silica gel as well as preparation method and application thereof
Through the coordination of specific component proportions, a stable three-dimensional network structure is constructed, which solves the problems of high shrinkage, easy degumming and high temperature and yellowing after curing of acrylate adhesives, and achieves low shrinkage, high stability and good transparency of organic silicone.
Patent Information
- Application Number
- CN202411809085.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
Acrylate adhesives have high shrinkage after curing, easily degummed, and are prone to yellowing in high temperature environments.
Components with specific mass ratios, including vinyl end-capped polydimethylsiloxane, side-containing polydimethylsiloxane, end-containing polydimethylsiloxane, optically active catalysts and inhibitors, are used to build a stable three-dimensional network structure to reduce volume shrinkage and improve stability and transparency.
It achieves low volume shrinkage, difficult to degumming, high transparency, and stable in high temperature environments, not easy to cause yellowing, good volume stability, high mechanical strength, and excellent appearance performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to an organic silica gel and a preparation method and application thereof. Background Art
[0002] Acrylic adhesives are currently the most widely used light-curing adhesives, which have the advantages of fast curing speed, low curing energy, and rich monomer diluent raw materials. However, during the use of acrylic adhesives, the shrinkage rate after curing is often high, generally > 2%; and it is easy to absorb moisture in the air and cause debonding; when used in an environment above 80°C, it is easy to produce yellowing. Summary of the invention
[0003] Based on this, it is necessary to provide organic silica gel which can reduce volume shrinkage, is not easy to debond and has high transparency, and its preparation method and application.
[0004] In one aspect of the present application, an organic silica gel is provided, wherein the raw materials for preparing the organic silica gel include the following components in parts by weight: 20 to 90 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of a cross-linking agent, 5 to 30 parts of a chain extender, 0.08 to 10 parts of an optically active catalyst, and 0.001 to 0.01 parts of an inhibitor; the cross-linking agent is a side-containing hydrogenated polydimethylsiloxane; and the chain extender is a terminal hydrogenated polydimethylsiloxane.
[0005] In the above-mentioned organic silica gel, vinyl-terminated polydimethylsiloxane is the main component for forming a cross-linked network structure. Side hydrogen-containing polydimethylsiloxane reacts with the active groups on the vinyl-terminated polydimethylsiloxane molecular chain to connect multiple linear or branched molecular chains together to construct a stable three-dimensional network structure. The end hydrogen-containing polydimethylsiloxane cooperates with the side hydrogen-containing polydimethylsiloxane and vinyl-terminated polydimethylsiloxane to further enhance the stability of the network structure and increase the cross-linking density; the optically active catalyst can accelerate the cross-linking process; the inhibitor can adjust the curing reaction rate to prevent the organic silica gel from curing prematurely. The above-mentioned organic silica gel cooperates with each other through specific components in a specific mass ratio to achieve synergistic effects, so that the organic silica gel not only has low shrinkage and good stability; but also is not easy to absorb moisture in the air in a humid environment, has high peeling strength, and is not easy to debond; even when used in an environment exceeding 80°C, it is not easy to produce yellowing, has low haze, and has high transparency. The organic silica gel has good volume stability, high mechanical strength, and excellent appearance performance, and has achieved unexpected comprehensive performance effects.
[0006] The above organic silicone also improves light curing and curing speed, and has the advantage of low temperature curing compared to traditional organic silicone. The above organic silicone can be cured by ultraviolet light, which can reduce production processes, improve production efficiency and reduce production costs.
[0007] The above-mentioned organic silica gel does not need to modify the raw materials. The preparation raw materials directly use common organic silicon polymers such as vinyl-terminated polydimethylsiloxane, side-containing hydrogen polydimethylsiloxane and terminal-containing hydrogen polydimethylsiloxane, thereby reducing the production cost and the complexity of the production process.
[0008] The above-mentioned organic silica gel can be used for a long time within the temperature range of -30 to 200°C, has a long service life, high stability and reliability, and can be applied to the preparation and processing of cutting-edge precision devices.
[0009] In some embodiments, the preparation raw materials are calculated by weight: the vinyl-terminated polydimethylsiloxane is 80 to 90 parts, the cross-linking agent is 1 to 5 parts, the chain extender is 5 to 23 parts, the optically active catalyst is 0.8 to 8 parts, and the inhibitor is 0.001 to 0.005 parts.
[0010] In some embodiments, the degree of polymerization of the vinyl-terminated polydimethylsiloxane is 100-6000; and / or, in the vinyl-terminated polydimethylsiloxane, the mass of the vinyl group accounts for 0.05%-1.0% of the mass of the vinyl-terminated polydimethylsiloxane.
[0011] In some embodiments, the polymerization degree of the side-containing hydrogenated polydimethylsiloxane is 15-25; and / or, in the side-containing hydrogenated polydimethylsiloxane, the mass of hydrogen atoms accounts for 0.08%-1.2% of the mass of the side-containing hydrogenated polydimethylsiloxane.
[0012] In some embodiments, the degree of polymerization of the hydrogen-terminated polydimethylsiloxane is 15-25; and / or, in the hydrogen-terminated polydimethylsiloxane, the mass of hydrogen atoms accounts for 0.28%-2.0% of the mass of the hydrogen-terminated polydimethylsiloxane.
[0013] In some embodiments, the optically active catalyst is at least one of trimethylcyclopentadienyl titanium, trimethylcyclopentadienyl platinum, manganese diacetylacetonate, copper acetylacetonate, cadmium acetylacetonate, Custer's catalyst and chloroplatinic acid.
[0014] In some embodiments, the inhibitor is at least one of tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, diallyl maleate, and diisooctyl maleate.
[0015] The second aspect of the present application provides a method for preparing the organic silica gel as described in the first aspect, comprising the following steps:
[0016] The vinyl-terminated polydimethylsiloxane, the crosslinking agent, the chain extender, the optically active catalyst and the inhibitor are mixed according to the mass fractions of the raw materials to prepare a mixture;
[0017] The mixed material is subjected to a degassing treatment to obtain the organic silica gel.
[0018] In some embodiments, a UV curing step is further included after the degassing treatment, and the UV curing step satisfies at least one of the following conditions:
[0019] (1) In the UV curing, the power of the UV light is 10W~200W;
[0020] (2) In the UV curing, the wavelength of the UV light is 200nm ~ 450nm;
[0021] (3) In the UV curing, the UV light irradiation time is 5s to 30s.
[0022] In some embodiments, the mixture satisfies at least one of the following conditions:
[0023] (1) The mixing is performed by vacuum mixing;
[0024] (2) The ambient temperature of the mixing material is 20°C to 35°C;
[0025] (3) The mixing time of the mixing is 0.5h~2h.
[0026] In some embodiments, the step of mixing and preparing the mixture comprises the following steps:
[0027] The optically active catalyst is first dissolved in the vinyl-terminated polydimethylsiloxane, and then the crosslinking agent, chain extender and inhibitor are added to mix.
[0028] The third aspect of the present application provides a use of the organic silica gel described in the first aspect in the preparation of electronic devices.
[0029] The fourth aspect of the present application provides an electronic device, comprising the organic silica gel as described in the first aspect, or the organic silica gel prepared by the preparation method of the organic silica gel as described in the second aspect. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant embodiments, wherein preferred embodiments of the present invention are given, but the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0032] Common photocuring adhesives include epoxy photocuring adhesives, polyurethane photocuring adhesives, polyester photocuring adhesives and acrylic photocuring adhesives. Among them, acrylic adhesives are the most widely used photocuring adhesives, which have the advantages of fast curing speed, low curing energy, and rich monomer diluent raw materials. However, acrylic adhesives often have a large shrinkage rate after curing, usually with a volume shrinkage rate of >2%, and are easy to absorb moisture in the air and cause debonding. When used in an environment above 80°C, they are prone to yellowing. Therefore, seeking an adhesive with a low volume shrinkage rate after curing, not easy to debond, and high transparency has become a technical problem that needs to be solved in the adhesive field.
[0033] Based on this, in the first aspect of the present application, an embodiment provides an organic silica gel, wherein the raw materials for preparing the organic silica gel include the following components in parts by weight: 20 to 90 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of a cross-linking agent, 5 to 30 parts of a chain extender, 0.08 to 10 parts of an optically active catalyst, and 0.001 to 0.01 parts of an inhibitor;
[0034] The cross-linking agent is a side-containing hydrogenated polydimethylsiloxane;
[0035] The chain extender is terminal hydrogen-containing polydimethylsiloxane.
[0036] The side hydrogen-containing polydimethylsiloxane is a polydimethylsiloxane in which the hydrogen atoms are located on the side chains of the polydimethylsiloxane molecule, rather than at the ends.
[0037] The molecular structure of side hydrogen-containing polydimethylsiloxane is as follows:
[0038]
[0039] Among them, m:n=0~500:3~1000; R1 is methyl, methoxy or ethoxy; R2 is methyl or phenyl.
[0040] The molecular structure of hydrogen-terminated polydimethylsiloxane is as follows:
[0041]
[0042] Among them, m:n=0~100:10~2000; R1 is methyl, methoxy or ethoxy; R2 is methyl or phenyl.
[0043] In the above-mentioned organic silica gel, vinyl-terminated polydimethylsiloxane is the main component for forming a cross-linked network structure. Side hydrogen-containing polydimethylsiloxane reacts with the active groups on the vinyl-terminated polydimethylsiloxane molecular chain to connect multiple linear or branched molecular chains together to construct a stable three-dimensional network structure. The end hydrogen-containing polydimethylsiloxane cooperates with the side hydrogen-containing polydimethylsiloxane and vinyl-terminated polydimethylsiloxane to further enhance the stability of the network structure and increase the cross-linking density; the optically active catalyst can accelerate the cross-linking process; the inhibitor can adjust the curing reaction rate to prevent the organic silica gel from curing prematurely. The above-mentioned organic silica gel cooperates with each other through specific components in a specific mass ratio to achieve synergistic effects, so that the organic silica gel not only has low shrinkage and good stability; but also is not easy to absorb moisture in the air in a humid environment, has high peeling strength, and is not easy to debond; even when used in an environment exceeding 80°C, it is not easy to produce yellowing, has low haze, and has high transparency. The organic silica gel has good volume stability, high mechanical strength, and excellent appearance performance, and has achieved unexpected comprehensive performance effects.
[0044] The above organic silicone also improves light curing and curing speed, and has the advantage of low temperature curing compared to traditional organic silicone. The above organic silicone can be cured by ultraviolet light, which can reduce production processes, improve production efficiency and reduce production costs.
[0045] The above-mentioned organic silica gel does not need to modify the raw materials. The preparation raw materials directly use common organic silicon polymers such as vinyl-terminated polydimethylsiloxane, side-containing hydrogen polydimethylsiloxane and terminal-containing hydrogen polydimethylsiloxane, thereby reducing the production cost and the complexity of the production process.
[0046] The above-mentioned organic silica gel can be used for a long time within the temperature range of -30 to 200°C, has a long service life, high stability and reliability, and can be applied to the preparation and processing of cutting-edge precision devices.
[0047] The above-mentioned organic silica gel can be used for a long time within the temperature range of -30 to 200°C, has a long service life, high stability and reliability, and can be applied to the preparation and processing of cutting-edge precision devices.
[0048] As an example, the weight percentage of the vinyl terminated polydimethylsiloxane can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, , 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts and 90 parts, or in the range consisting of any two of the above values as end values. The mass fraction of the vinyl-terminated polydimethylsiloxane is preferably 80 parts to 90 parts.
[0049] As an example, the weight fraction of the crosslinking agent can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts and 10 parts, or within the range consisting of any two of the above values as end values. The weight fraction of the crosslinking agent is preferably 1 part to 5 parts.
[0050] As an example, the weight percentage of the chain extender can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts and 30 parts, or a range consisting of any two of the above values as end values. The weight percentage of the chain extender is preferably 5 to 23 parts.
[0051] As an example, the mass fraction of the optically active catalyst can be 0.08 parts, 0.1 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts and 10 parts, or a range consisting of any two of the above values as end values. The mass fraction of the optically active catalyst is preferably 0.8 parts to 8 parts.
[0052] As an example, the mass fraction of the inhibitor can be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009 and 0.01, or a range consisting of any two of the above values as end values. The mass fraction of the inhibitor is preferably 0.001 to 0.005.
[0053] In some embodiments, the raw materials for preparation are calculated by weight, and the vinyl-terminated polydimethylsiloxane is 80 to 90 parts, the cross-linking agent is 1 to 5 parts, the chain extender is 5 to 23 parts, the optically active catalyst is 0.8 to 8 parts, and the inhibitor is 0.001 to 0.005 parts. The organic silica gel with this component and mass ratio has a smaller volume shrinkage, higher peel strength, colorless and transparent, low haze, high transmittance, and better volume stability, mechanical properties and appearance properties.
[0054] In some embodiments, the degree of polymerization of the vinyl terminated polydimethylsiloxane is 100 to 6000. The degree of polymerization of the vinyl terminated polydimethylsiloxane is preferably 200 to 400. The vinyl terminated polydimethylsiloxane at this degree of polymerization is more conducive to forming a stable network structure, reducing the curing volume shrinkage, and improving the adhesion of the organic silicone.
[0055] In some embodiments, the mass of the vinyl group in the vinyl-terminated polydimethylsiloxane accounts for 0.05% to 1.0% of the mass of the vinyl-terminated polydimethylsiloxane, preferably 0.05% to 0.26%. The vinyl-terminated polydimethylsiloxane with this vinyl mass content is more conducive to forming a stable network structure, reducing the curing volume shrinkage, and improving the adhesion of the organic silicone.
[0056] In some embodiments, the degree of polymerization of the vinyl-terminated polydimethylsiloxane is 200-600, and the mass of the vinyl group accounts for 0.05%-0.26% of the mass of the vinyl-terminated polydimethylsiloxane. When the degree of polymerization is 200-600 and the mass content of the vinyl group is 0.05%-0.26%, it can further promote the construction of a stable network structure and improve the adhesion of the organic silica gel.
[0057] In some embodiments, the degree of polymerization of the side hydrogen-containing polydimethylsiloxane is 15-25.
[0058] In some embodiments, the mass of hydrogen atoms in the side-containing hydrogenated polydimethylsiloxane accounts for 0.08% to 1.2% of the mass of the side-containing hydrogenated polydimethylsiloxane. Using the side-containing hydrogenated polydimethylsiloxane as a chain extender can improve the tensile strength of organic silica gel, increase the crosslinking efficiency, and enhance the chemical stability of silica gel.
[0059] In some embodiments, the degree of polymerization of the hydrogen-terminated polydimethylsiloxane is 15-25.
[0060] In some embodiments, the mass of hydrogen atoms in the terminal hydrogenated polydimethylsiloxane accounts for 0.28% to 2.0% of the mass of the terminal hydrogenated polydimethylsiloxane. Using the terminal hydrogenated polydimethylsiloxane as a chain extender can improve the tensile strength of organic silica gel, increase the crosslinking efficiency, and enhance the chemical stability of silica gel.
[0061] In some embodiments, the optically active catalyst is at least one of a Custer catalyst, an acetone solution of chloroplatinic acid, a complex of trimethylcyclopentadienyl platinum, a complex of trimethylcyclopentadienyl titanium, a derivative of copper acetylacetonate complex, a derivative of cadmium acetylacetonate complex, and a derivative of aromatic hydrocarbon-substituted cyclopentadienyl complex.
[0062] In some embodiments, the optically active catalyst is at least one of trimethylcyclopentadienyl titanium, trimethylcyclopentadienyl platinum, diacetylacetonate manganese, copper acetylacetonate, cadmium acetylacetonate, Custer's catalyst and chloroplatinic acid. The optically active catalyst can accelerate the curing reaction, so that the organic silica gel of the present application can be cured by ultraviolet light, improve the transparency of the organic silica gel, improve the optical properties, and can also enhance the light resistance of the organic silica gel and inhibit photooxidation reactions.
[0063] In some embodiments, the optically active catalyst is trimethylcyclopentadienyltitanium or manganese bisacetylacetonate.
[0064] In some embodiments, the inhibitor is at least one of tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, diallyl maleate, and diisooctyl maleate.
[0065] In some embodiments, the degree of polymerization of the vinyl-terminated polydimethylsiloxane is 200-600, and the mass of the vinyl group accounts for 0.05%-0.26% of the mass of the vinyl-terminated polydimethylsiloxane;
[0066] The agent is a side-containing hydrogenated polydimethylsiloxane, and the mass of hydrogen atoms in the side-containing hydrogenated polydimethylsiloxane accounts for 0.08% to 0.18% of the mass of the side-containing hydrogenated polydimethylsiloxane; the chain extender is a terminal-containing hydrogenated polydimethylsiloxane, and the mass of hydrogen atoms in the terminal-containing hydrogenated polydimethylsiloxane accounts for 0.43% to 0.66% of the mass of the terminal-containing hydrogenated polydimethylsiloxane; the optically active catalyst is trimethyl cyclopentadienyl titanium. With this combination of raw materials, the organic silica gel obtains a lower volume shrinkage and better appearance performance, and does not produce the phenomenon of yellowing.
[0067] The second aspect of the present application provides a method for preparing the organic silica gel as described in the first aspect, comprising the following steps:
[0068] The vinyl-terminated polydimethylsiloxane, the crosslinking agent, the chain extender, the optically active catalyst and the inhibitor are mixed according to the mass fractions of the raw materials to prepare a mixture;
[0069] The mixed material is subjected to a degassing treatment to obtain the organic silica gel.
[0070] In some embodiments, a UV curing step is further included after the degassing treatment, and during the UV curing, the power of the UV light is 10W to 200W.
[0071] As an example, the power of the ultraviolet light can be 10W, 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W, 190W and 200W, or within a range consisting of any two of the aforementioned values as end values.
[0072] After UV curing at this power, the curing speed, curing depth and mechanical properties of silicone rubber can be well balanced.
[0073] In some embodiments, in the UV curing, the wavelength of the UV light is 200nm ~ 450nm.
[0074] As an example, the wavelength of the ultraviolet light can be 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 365nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm and 450nm, or within a range consisting of any two of the foregoing values as end values.
[0075] After UV curing at this wavelength, the organic silicone will form a better cross-linked network structure, thus having better mechanical properties such as tensile strength and elastic modulus. It can also promote the chemical bonds in the organic silicone to form a good structure, making it more tolerant to environmental factors such as chemical reagents and humidity.
[0076] In some embodiments, during the UV curing, the UV light irradiation time is 5s to 30s.
[0077] As an example, the irradiation time of ultraviolet light can be 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 20s, 21s, 22s, 23s, 24s, 25s, 26s, 27s, 28s, 29s and 30s, or within the range formed by any two of the aforementioned values as end values.
[0078] Under this irradiation time, the cured silicone not only has good stability and excellent mechanical properties, but also has high curing uniformity, so that the silicone can achieve good curing uniformity in both the thickness direction and the plane direction.
[0079] In some embodiments, the mixing is performed by vacuum mixing.
[0080] Furthermore, the mixing is performed by vacuum mixing, and the vacuum degree is -0.1MPa ~-0.01MPa.
[0081] In some embodiments, the ambient temperature of the mixture is 20°C to 35°C;
[0082] In some embodiments, the mixing time of the mixing is 0.5h~2h.
[0083] As an example, the mixing time can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h and 2.0h, or a range consisting of any two of the above values as end values. The mixing time is preferably 1 h to 1.5 h.
[0084] In some embodiments, the step of mixing and preparing the mixture comprises the following steps:
[0085] The optically active catalyst is first dissolved in the vinyl-terminated polydimethylsiloxane, and then the crosslinking agent, chain extender and inhibitor are added to mix.
[0086] The third aspect of the present application provides a use of the organic silica gel described in the first aspect in the preparation of electronic devices.
[0087] The above-mentioned organic silica gel can be used for bonding components, packaging chips, sealing and moisture-proofing in electronic devices, etc.
[0088] The fourth aspect of the present application provides an electronic device, comprising the organic silica gel as described in the first aspect, or the organic silica gel prepared by the preparation method of the organic silica gel as described in the second aspect.
[0089] The above-mentioned electronic devices include, but are not limited to, solar cell modules, solar lamps, mobile phones, computers, televisions, refrigerators, air conditioners, automotive electronic devices, PC display panels, vehicle-mounted display screens and mobile phone display screens.
[0090] When the above-mentioned organic silicone is used as an adhesive or packaging adhesive in a display screen, the reliability of the display screen can be improved, thereby extending the service life of the display screen product because the organic silicone can be used for a long time in the range of -30~200°C. Its good optical transparency has a high transmittance to visible light and will not reduce the brightness and color saturation of the display screen, making the image presented to the user clearer and more vivid.
[0091] The following are specific embodiments.
[0092] Example 1
[0093] Ingredients: Weigh 90 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi1320) with a degree of polymerization of 200 and a vinyl content of 0.26%, 5 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-DH07) with a degree of polymerization of 20 and a hydrogen content of 0.08%, 5 parts by weight of side hydrogen-containing polydimethylsiloxane (RH-H503) with a degree of polymerization of 20 and a hydrogen content of 0.56%, 8 parts by weight of (trimethyl) cyclopentadienyl titanium, and 0.003 parts by weight of ethynyl cyclohexanol;
[0094] Mixing: Add the above raw materials into a mixer respectively, stir at a speed of 800r / min for 1.5h under a vacuum degree of -0.095MPa and a temperature of 25°C. Filter the obtained mixture and pack it into designated containers in a dark place;
[0095] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, coat or encapsulate it and then cure it under LED ultraviolet light with a power of 50W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0096] Example 2
[0097] Ingredients: Weigh 90 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi301) with a polymerization degree of 600 and a vinyl content of 0.06%, 1 part by weight of side hydrogen-containing polydimethylsiloxane (RH-H33) with a polymerization degree of 20 and a hydrogen content of 0.18%, 6 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-H518) with a polymerization degree of 20 and a hydrogen content of 0.18%, 0.8 parts by weight of manganese diacetylacetonate, and 0.002 parts by weight of methylbutynol;
[0098] Mixing: Add the above raw materials into a blender respectively, stir at a speed of 700r / min for 1.0h under a vacuum degree of -0.052 MPa and a temperature of 20-35°C. Filter the obtained product and pack it into designated containers in the dark;
[0099] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, after coating or potting, cure it under any form of ultraviolet light with a power of 10W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0100] Example 3
[0101] Ingredients: 82 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi303) with a polymerization degree of 500 and a vinyl content of 0.12%, 3 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-DH07) with a polymerization degree of 20 and a hydrogen content of 0.08%, 5 parts by weight of side hydrogen-containing polydimethylsiloxane (RH-H502) with a polymerization degree of 20 and a hydrogen content of 0.66%, 8 parts by weight of (trimethyl) cyclopentadienyl titanium, and 0.003 parts by weight of ethynyl cyclohexanol;
[0102] Mixing: Add the above raw materials into a blender respectively, stir at a speed of 800r / min for 1.5h under a vacuum degree of -0.095MPa and a temperature of 25°C. Filter the obtained product and pack it into designated containers in a dark place;
[0103] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, after coating or potting, cure it under LED ultraviolet light with a power of 50W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0104] Example 4
[0105] Ingredients: 70 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi1323) with a polymerization degree of 100 and a vinyl content of 0.56%, 8 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-H33) with a polymerization degree of 20 and a hydrogen content of 0.18%, 23 parts by weight of side hydrogen-containing polydimethylsiloxane (RH-H3) with a polymerization degree of 20 and a hydrogen content of 0.28%, 0.8 parts by weight of (trimethyl) cyclopentadienyl titanium, and 0.003 parts by weight of ethynyl cyclohexanol;
[0106] Mixing: Add the above raw materials into a blender respectively, stir at a speed of 700 r / min for 1.0 h under a vacuum degree of -0.052 MPa and a temperature of 20-35°C. Filter the obtained product and pack it into designated containers in a dark place;
[0107] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, after coating or potting, cure it under any form of ultraviolet light with a power of 10W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0108] Example 5
[0109] Ingredients: 90 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi1320) with a polymerization degree of 400 and a vinyl content of 0.26%, 5 parts by weight of side hydrogen-containing polydimethylsiloxane (RH-DH07) with a polymerization degree of 20 and a hydrogen content of 0.08%, 5 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-H503) with a polymerization degree of 20 and a hydrogen content of 0.56%, 0.08 parts by weight of (trimethyl) cyclopentadienyl titanium, and 0.001 parts by weight of diallyl maleate;
[0110] Mixing: Add the above raw materials into a blender respectively, stir at a speed of 800r / min for 1.5h under a vacuum degree of -0.095MPa and a temperature of 25°C. Filter the obtained product and pack it into designated containers in a dark place;
[0111] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, after coating or potting, cure it under LED ultraviolet light with a power of 50W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0112] Example 6
[0113] Ingredients: 90 parts by weight of vinyl-terminated polydimethylsiloxane (RH-Vi1320) with a polymerization degree of 200 and a vinyl content of 0.26%, 5 parts by weight of side hydrogen-containing polydimethylsiloxane (RH-DH07) with a polymerization degree of 20 and a hydrogen content of 0.08%, 5 parts by weight of terminal hydrogen-containing polydimethylsiloxane (RH-H503) with a polymerization degree of 20 and a hydrogen content of 0.56%, 8 parts by weight of (trimethyl) cyclopentadienyl titanium, and 0.003 parts by weight of ethynyl cyclohexanol;
[0114] Mixing: Add the above raw materials into a blender respectively, stir at a speed of 700 r / min for 1.0 h under a vacuum degree of -0.052 MPa and a temperature of 20-35°C. Filter the obtained product and pack it into designated containers in a dark place;
[0115] Degassing and curing: Place the mixture in a high-speed vacuum degassing machine, degas at a speed of 1500r / min, and finally fill it. When in use, after coating or potting, cure it under any form of ultraviolet light with a power of 10W and a wavelength of 365nm for 10s to obtain organic silica gel.
[0116] Example 7
[0117] Example 7 is substantially the same as Example 1, except that the amount of vinyl-terminated polydimethylsiloxane is 20 parts by mass.
[0118] Comparative Example 1
[0119] 70g of vinyl silicone oil containing terminal mercapto groups, 25g of a copolymer of thioalkanol and alkyl and / or aryl siloxane, 5.0g of vinyl silicone oil, 0.2g of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 0.1g of 2-chlorothioxanthen-9-one, 0.5g of acrylic acid / epoxy modified silicone polysiloxane (XL-710), and 0.01g of tricresyl phosphate were heated to 45-55°C and stirred to dissolve; the remaining raw materials were then added, added to a stirrer under vacuum and dispersed at high speed, filtered and packaged to obtain a UV-curable silicone liquid optical adhesive composition.
[0120] Comparative Example 2
[0121] Comparative Example 2 is substantially the same as Example 1, except that an equal amount of methylphenylchlorosilane is used to replace the vinyl-terminated polydimethylsiloxane.
[0122] Comparative Example 3
[0123] Comparative Example 3 is substantially the same as Example 1, except that an equal mass fraction of functionalized acryloxyethyl polydimethylsiloxane (KH-570) is used to replace the side hydrogen-containing polydimethylsiloxane.
[0124] Comparative Example 4
[0125] Comparative Example 4 is substantially the same as Example 1, except that an equal amount of dimethyldimethoxysilane is used to replace the terminal hydrogen-containing polydimethylsiloxane.
[0126] The organic silica gels prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested for transmittance, volume shrinkage, haze, tensile strength and peel strength. The test results are shown in Table 1 below.
[0127] Among them, the test conditions or test standards for each performance test item are:
[0128] The transmittance test standard is JIS K7105-81;
[0129] The volume shrinkage test standard is ASTM C1241-14;
[0130] The haze test standard is JIS K 7136;
[0131] The tensile strength test standard is JIS K 6815-1;
[0132] The peel strength test standard is GB / T 2792-2014.
[0133] Table 1
[0134]
[0135] As can be seen from Table 1 above, the organic silica gels prepared in Examples 1 to 7 have low shrinkage, high mechanical strength, good appearance transparency, and are not prone to yellowing due to the mutual cooperation and synergistic effect between specific components in specific mass ratios. The volume shrinkage of the organic silica gels prepared in Comparative Examples 1, 3, and 4 is relatively large, and the organic silica gel prepared in Comparative Example 2 is milky white with low transparency.
[0136] It can be seen from Examples 1 to 7 that when the degree of polymerization of the vinyl-terminated polydimethylsiloxane is 100 to 6000, the mass of the vinyl group in the vinyl-terminated polydimethylsiloxane accounts for 0.05% to 1% of the mass of the vinyl-terminated polydimethylsiloxane; the mass of the hydrogen atoms in the side hydrogen-containing polydimethylsiloxane accounts for 0.08% to 1.2% of the mass of the side hydrogen-containing polydimethylsiloxane; the mass of the hydrogen atoms in the terminal hydrogen-containing polydimethylsiloxane accounts for 0.28% to 2.0% of the mass of the terminal hydrogen-containing polydimethylsiloxane, the volume shrinkage of the organic silica gel is lower and the peel strength is higher.
[0137] It can be seen from Examples 1 to 3 and Example 6 that the degree of polymerization of the vinyl-terminated polydimethylsiloxane is 200 to 600, and the mass of the vinyl group accounts for 0.05% to 0.26% of the mass of the vinyl-terminated polydimethylsiloxane; the mass of the hydrogen atoms in the side hydrogen-containing polydimethylsiloxane accounts for 0.08% to 0.18% of the mass of the side hydrogen-containing polydimethylsiloxane; when the mass of the hydrogen atoms in the terminal hydrogen-containing polydimethylsiloxane accounts for 0.43% to 0.66% of the mass of the terminal hydrogen-containing polydimethylsiloxane, the organic silica gel obtains a lower volume shrinkage and better comprehensive mechanical and appearance properties.
[0138] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0139] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An organic silica gel, characterized in that: The raw materials for preparing the organic silica gel include the following components in parts by weight: 20 to 90 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of a cross-linking agent, 5 to 30 parts of a chain extender, 0.08 to 10 parts of an optically active catalyst, and 0.001 to 0.01 parts of an inhibitor; The cross-linking agent is a side-containing hydrogenated polydimethylsiloxane; The chain extender is terminal hydrogen-containing polydimethylsiloxane.
2. The organic silica gel according to claim 1, characterized in that: The raw materials for preparation are calculated by weight as follows: 80 to 90 parts of the vinyl-terminated polydimethylsiloxane, 1 to 5 parts of the cross-linking agent, 5 to 23 parts of the chain extender, 0.8 to 8 parts of the optically active catalyst, and 0.001 to 0.005 parts of the inhibitor.
3. The organic silica gel according to claim 1, characterized in that: The degree of polymerization of the vinyl-terminated polydimethylsiloxane is 100-6000; and / or, in the vinyl-terminated polydimethylsiloxane, the mass of the vinyl group accounts for 0.05%-1.0% of the mass of the vinyl-terminated polydimethylsiloxane.
4. The organic silica gel according to claim 1, characterized in that: The polymerization degree of the side-containing hydrogenated polydimethylsiloxane is 15-25; and / or, in the side-containing hydrogenated polydimethylsiloxane, the mass of hydrogen atoms accounts for 0.08%-1.2% of the mass of the side-containing hydrogenated polydimethylsiloxane.
5. The organic silica gel according to claim 1, characterized in that: The degree of polymerization of the terminal hydrogen-containing polydimethylsiloxane is 15-25; and / or, in the terminal hydrogen-containing polydimethylsiloxane, the mass of hydrogen atoms accounts for 0.28%-2.0% of the mass of the terminal hydrogen-containing polydimethylsiloxane.
6. The organic silica gel according to any one of claims 1 to 5, characterized in that: The optically active catalyst is at least one of trimethylcyclopentadienyl titanium, trimethylcyclopentadienyl platinum, manganese diacetylacetonate, copper acetylacetonate, cadmium acetylacetonate, Custer catalyst and chloroplatinic acid.
7. The organic silica gel according to any one of claims 1 to 5, characterized in that: The inhibitor is at least one of tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, diallyl maleate and diisooctyl maleate.
8. A method for preparing the organic silica gel according to any one of claims 1 to 7, characterized in that: The steps include: The vinyl-terminated polydimethylsiloxane, the crosslinking agent, the chain extender, the optically active catalyst and the inhibitor are mixed according to the mass fractions of the raw materials to prepare a mixture; The mixed material is subjected to a degassing treatment to obtain the organic silica gel.
9. The method for preparing organic silica gel according to claim 8, characterized in that: After the degassing treatment, an ultraviolet curing step is also included, and the ultraviolet curing step meets at least one of the following conditions: (1) In the UV curing, the power of the UV light is 10W~200W; (2) In the UV curing, the wavelength of the UV light is 200nm ~ 450nm; (3) In the UV curing, the UV light irradiation time is 5s to 30s.
10. The method for preparing organic silica gel according to claim 8, characterized in that: The mixture satisfies at least one of the following conditions: (1) The mixing is performed by vacuum mixing; (2) The ambient temperature of the mixing material is 20°C to 35°C; (3) The mixing time of the mixing is 0.5h~2h.
11. The method for preparing organic silica gel according to any one of claims 8 to 10, characterized in that: The mixing step of preparing the mixed material comprises the following steps: The optically active catalyst is first dissolved in the vinyl-terminated polydimethylsiloxane, and then the crosslinking agent, chain extender and inhibitor are added to mix.
12. Use of the organic silica gel according to any one of claims 1 to 7 in the preparation of electronic devices.
13. An electronic device, characterized in that: The organic silica gel comprises the organic silica gel as described in any one of claims 1 to 7, or the organic silica gel prepared by the preparation method of the organic silica gel as described in any one of claims 8 to 11.